BIMBINGAN DAN PEMBINAAN PENYUSUNAN SISTEM DAN PROSEDUR AKUNTANSI DAN OPERASIONAL: KOPERASI KONSUMEN LUMBUNG SAHABAT TERANG KOTA BEKASI - Bangar Hasioan Sianipar, Panata (Universitas katolik Musi Charitas, 2023)
Supervision is important element in an organization, where one of the supervision tools are systemsand procedures. Systems and procedures help the process of control more effective and efficient.The Lumbung Sahabat Terang Consumer Cooperative has a savings and loan business unit with325 active members. This community service program aims to see the rapid growth of cooperativesneeds good supervision from supervisors and management; that’s the background of thiscommunity service. This need prompted the supervisory board and management to invite the authorto conduct guidance and coaching the member of cooperative supervisors’ board and management.Training and guiding were used as the method in preparing adequate accounting and operationalprocedures for cooperative. The provided training was based on the management control systemsand accounting theory, while guidance was carried out by practicing making simple procedures.The direct result of this community service was that participants can compile systems andprocedures in the flowchart of transaction documents for receiving deposits and disbursing loanfunds by administrators and supervisors with direct guidance. The conclusion revealed that system,accounting and operational procedures for cooperatives help supervisors to evaluate themanagement's control performance. If adequate accounting and operational systems andprocedures can be developed, it is hoped that good cooperative governance can be implemented.